2020
DOI: 10.3389/fcell.2020.00120
|View full text |Cite
|
Sign up to set email alerts
|

Function of PIN1 in Cancer Development and Its Inhibitors as Cancer Therapeutics

Abstract: Peptidyl-prolyl isomerase (PIN1) specifically binds and isomerizes the phosphorylated serine/threonine-proline (pSer/Thr-Pro) motif, which results in the alteration of protein structure, function, and stability. The altered structure and function of these phosphorylated proteins regulated by PIN1 are closely related to cancer development. PIN1 is highly expressed in human cancers and promotes cancer as well as cancer stem cells by breaking the balance of oncogenes and tumor suppressors. In this review, we disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 151 publications
(184 reference statements)
0
31
0
Order By: Relevance
“…An increasing body of evidence shows that β-catenin not only increases cell proliferation but also promotes migration and invasion in cancer cells [ 66 , 157 , 161 ]. Therefore, Pin1 promotes invasion, metastasis and even other malignant tumor processes partly through the upregulation of β-catenin-mediated signaling cascades [ 19 , 68 , 150 ]. Transforming growth factor (TGF)-β plays a critical role in tumor metastasis [ 162 , 163 , 164 , 165 ] and Pin1 has been found to upregulate TGF-β by stabilizing its mRNA [ 166 ].…”
Section: Dysregulation Of Pin1 Signaling In Tumorigenesismentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing body of evidence shows that β-catenin not only increases cell proliferation but also promotes migration and invasion in cancer cells [ 66 , 157 , 161 ]. Therefore, Pin1 promotes invasion, metastasis and even other malignant tumor processes partly through the upregulation of β-catenin-mediated signaling cascades [ 19 , 68 , 150 ]. Transforming growth factor (TGF)-β plays a critical role in tumor metastasis [ 162 , 163 , 164 , 165 ] and Pin1 has been found to upregulate TGF-β by stabilizing its mRNA [ 166 ].…”
Section: Dysregulation Of Pin1 Signaling In Tumorigenesismentioning
confidence: 99%
“…The WW domain preferentially binds to pSer/Thr-Pro containing peptide sequences, while the catalytic domain isomerizes the prolyl bond in the pSer/Thr-Pro motif [ 14 , 16 ]. Pin1 was initially identified as being involved in cell cycle progression, but mounting evidence has shown that Pin1-mediated prolyl isomerization plays a crucial role in diverse biological processes, including cell cycle regulation, cell growth, differentiation, immune responses, stemness, and even tumorigenesis [ 8 , 17 , 18 , 19 ]. Moreover, Pin1 is commonly overexpressed in most cancers and high levels of Pin1 expression is correlated with poor prognosis in various cancers [ 10 , 11 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant Pin1 elevation has been shown to be involved in many signaling events such as cell cycle coordination, chromosome instability, proliferation, migration, metastasis, and apoptosis in cancer (Zhou and Lu, 2016). Indeed, Pin1 is known to activate 56 oncogenes and inactivate 26 tumor suppressors by regulating their activity, protein interaction, stability, and cellular localization (Cheng and Tse, 2019;Yu et al, 2020). Pin1 overexpression in mammary gland induces chromosome instability and leads to breast cancer development and Pin1 ablation effectively prevents tumorigenesis by overexpressing Neu in animal models (Wulf et al, 2004;Suizu et al, 2006).…”
Section: Pin1 In Diagnostic and Therapeutic Strategies For Admentioning
confidence: 99%
“…Peptidyl-prolyl cis-trans isomerase NIMA-interacting 1 (Pin1), an isomerase that specifically recognizes the serine/threonine-proline motif, is overexpressed in several cancers including pancreatic, breast, and prostate and its expression correlates with poor clinical outcomes [ 129 , 130 , 131 ]. Furthermore, Pin1 promotes several hallmarks of cancer through inactivating 26 tumor suppressors and activating 56 oncogenes [ 132 , 133 ]. By catalyzing the cis/trans conformational change of the target protein, such as Myc, isomerases like Pin1 gain control of the target protein’s stability, activity, and localization [ 134 ].…”
Section: Disrupting Myc Stability To Inhibit Its Actions As a Tranmentioning
confidence: 99%